Ferroptosis in neurodegenerative diseases: potential mechanisms of exercise intervention - Tang, Shaokai; Zhang, Jianhua; Chen, Jiawei; Zhou, Zeng; Lin, Qinqin (Frontiers in Cell and Developmental Biology, 2025)
Neurodegenerative diseases represent a major global cause of mortality and disability. These disorders are characterized by complex pathogenesis and currently lack effective therapeutic strategies. Iron, a vital trace element for normal brain function, has been implicated in the pathogenesis of neurodegenerative diseases via the ferroptosis pathway. Emerging evidence indicates that exercise can suppress ferroptosis directly or indirectly by regulating iron metabolism, oxidative stress, and exerkine expression, thereby conferring neuroprotection. This review summarizes current insights into the role of ferroptosis in neurodegenerative diseases and explores the mechanisms by which exercise modulates the ferroptosis pathway, offering a scientific rationale for exercise-based interventions in brain health.